Unjuk Kerja Alat Pemipil Jagung Tanikaya Model TK PJK-2T dengan Mesin Penggerak Merek Kubota Tipe RD 65DI-1S di Desa Tanjung Sidupa Kecamatan Pinogaluman Kabupaten Bolaang Mongondow Utara - Lalensang, Christanti; Rantung, Ruland A.; Ludong , Daniel P. M. (Jurnal Teknologi Pertanian (Agricultural Technology Journal), 2025)
This study aims to test and analyze the performance of the Tanikaya Model TK PJK-2T corn sheller powered by a Kubota Type RD 65DI-1S engine including 1) the working capacity of the machine 2) fuel consumption, and 3) shelling yield. The research was conducted in Tanjung Sidupa Village, Pinogaluman District, using the experimental method. Data were collected in tabular form and processed descriptively. Data collection was carried out in three replications. research results showed that the working capacity of the corn shelling machine at a rotational speed of 1197 rpm was 1034 kg/hour. The working capacity of the shelling machine at a speed of 938.8 rpm was 937.50 kg/hour, and at a rotational speed of 727.4 rpm, it was 833.33 kg/hour. Fuel consumption at 1197 rpm was 109.3 ml, at 938.8 rpm was 103.3 ml, and at 727.4 rpm was 76.33 ml. The highest average shelling yield was achieved at 1197 rpm (82%), while the lowest was at 727.4 rpm (78.50%). Keywords: Performance of Corn Sheller; Tanikaya Corn Sheller; Kubota Engine.